HEATING OPTIMIZATION SYSTEM IN A SMART HOME BASED ON FUZZY LOGIC AND INTEGRATION WITH CLOUD SERVICES (Computer systems and information technologies, 2025)
This paper proposes a heating optimization system in a smart home based on fuzzy logic and integration with cloud services. According to the results obtained, the use of fuzzy logic significantly improves the stability of the temperature in the house, which is important for the comfort of residents. For the experiments, two models were compared - the basic heating model and the model based on fuzzy logic. The basic system, which does not take into account variable factors with such a level of flexibility, leads to large and sharp temperature fluctuations, which can create discomfort and increase energy consumption. In contrast, the model with fuzzy logic demonstrates a smoother and more stable temperature control, which allows you to significantly reduce energy costs.
Keywords: heating system optimization; fuzzy logic; control system